Legal Ethics and Human Dignity - Luban, David (Cambridge University, 2013)
David Luban is one of the world's leading scholars of legal ethics. In this collection of his most significant papers from the past 25 years, he ranges over such topics as the moral psychology of organizational evil, the strengths and weaknesses of the adversary system, and jurisprudence from the lawyer's point of view. His discussion combines philosophical argument, legal analysis, and many cases drawn from actual law practice, and he defends a theory of legal ethics that focuses on lawyers' role in enhancing human dignity and human rights. In addition to an analytical introduction, the volume includes two major previously unpublished papers, including a detailed critique of the US government lawyers who produced the notorious "torture memos." It will be of interest to a wide range of readers in both philosophy and law